2017
DOI: 10.1017/jns.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of HbA1c levels by fucoxanthin-enriched akamoku oil possibly involves the thrifty allele of uncoupling protein 1 (UCP1): a randomised controlled trial in normal-weight and obese Japanese adults

Abstract: Lifestyle-related problems are becoming a major health threat in East Asian countries. Therefore, finding an efficacious nutraceutical for this population is important. One candidate is fucoxanthin (Fx), a carotenoid abundantly found in edible brown seaweed that has been associated with a number of valuable health-promoting benefits. Unfortunately, clinical studies of Fx are limited. In the present study, we aimed to evaluate the effects of Fx on obesity-related parameters in Japanese subjects harbouring an SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…In this clinical trial, we observed no effect of Harudori-kombu on blood glucose profiles. A previous clinical trial has demonstrated a significant decline in HbA1c levels in the 2 mg/day fucoxanthin group compared with that in the placebo group [6]. Moreover, adiponectin levels were associated with blood glucose profiles, such as insulin resistance and glucose uptake.…”
Section: Discussionmentioning
confidence: 88%
“…In this clinical trial, we observed no effect of Harudori-kombu on blood glucose profiles. A previous clinical trial has demonstrated a significant decline in HbA1c levels in the 2 mg/day fucoxanthin group compared with that in the placebo group [6]. Moreover, adiponectin levels were associated with blood glucose profiles, such as insulin resistance and glucose uptake.…”
Section: Discussionmentioning
confidence: 88%
“…Mikami et al reported clinical trial results on anti-diabetic effect by fucoxanthin administration [33]. Fucoxanthin was administered 1 mg or 2 mg/day for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike carotenes, which are known to be converted into Vitamin A, the accumulation and bioavailability of FXN and ASX vary among animal and human models [37,77]. The accumulation of dietary FXN and ASX (either intact or as metabolites) in the tissues have been reported in animal models [78][79][80][81], but few recent studies are available on bioavailability in humans [82,83]. Hence, it is inexpedient to draw a relative conclusion on the quantity of xanthophylls available for absorption in animal and human models.…”
Section: Antioxidant Properties and Bioaccessibility Of Seaweed Xanthmentioning
confidence: 99%